Optimum mix ratio of concrete brick using rice husk ash - Norfazlin Binti Husin (School of Environmental Engineering, University Malaysia Perlis, 2014)
This study focused on the effect of using rice husk ash as a additive material to cement in production of concrete brick, to determine the optimum mix ratio of concrete brick and the compressive strength of concrete brick and also the reduce environment pollution makes one of the factors of this study.